PEMBAGIAN DAN PENGELOLAAN ZAKAT - Muhammad Farid (AL-IQTISHAD, 2020)
AbstractZakat maal must in charity when it reaches nisab and time is a wealth of gold,silver, money, trade, company, Rikaz and all kinds of profitable operating resultsand the distribution of alms to 8 asnaf is mandatory and can be developed for theneeds, interests and progress of the people /Muslim community in accordance withthe times.Kata Kunci: Pembagian; pengelolaan zakat.